Pandemic-Related Experiences and Stress Among Children's Hospital Staff Predict Psychosocial Risk. Issue 2 (31st January 2022) - Grasso, Damion J.; Lewin, Matthew M.; Adams, Basia; Lapidus, Garry
SUMMARY: Goal: COVID-19 has imposed unique challenges for healthcare workers who have faced increased risk of exposure to the virus, heightened work demands, and disruptions in work–life balance. For some healthcare workers, these challenges may have contributed to increased stress, burnout, and psychosocial impairment, including symptoms of depression and anxiety. The current study addresses a knowledge gap of associations between pandemic-related experiences and psychosocial risk among medical and nonmedical pediatric healthcare staff. Methods: A sample of 369 staff (90% female) employed at an acute care, freestanding pediatric hospital in Connecticut completed an online survey. The survey assessed specific pandemic-related experiences and perceived impact with the Epidemic-Pandemic Impacts Inventory, and depression and anxiety risk with the 2-item Patient Health Questionnaire depression screen and 2-item Generalized Anxiety Disorder screen, respectively. Enrollment and survey completion occurred over a 6-week period during the pandemic (summer 2020). Principal Findings: High rates of adverse pandemic-related experiences included workplace experiences (e.g., inadequate support, interpersonal difficulties), home life (e.g., childcare difficulties, partner conflict), and experiences reflecting social isolation and quarantine, child and adult mental health difficulties, increased alcohol or substance use, and unhealthy lifestyle behaviors. Medical relative to nonmedical staff reported significantly more adverse and fewer positive experiences, and a significantly higher perceived negative impact of workplace experiences. A positive screen for depression or anxiety was significantly predicted by cumulative adverse workplace experiences ( OR = 1.15), changes in emotional/physical health ( OR = 1.35), and perceived negative impact of workplace experiences ( OR = 1.32). Applications to Practice: The present study joins recent reports of increased adverse experiences and psychosocial outcomes among healthcare workers during the COVID-19 pandemic. Findings underscore the need for pediatric hospitals to innovate ways to reduce burden and connect staff to mental health services during similar public health crises. Such services might include (1) assisting healthcare staff to navigate disruptions in their home and social lives as a result of new challenges faced at work, (2) adapting the hospital environment and culture to mitigate stress experienced by staff because of these challenges, and (3) bolstering mental health screening and services to address exacerbated or emerging mental health symptoms, such as depression and anxiety.